Comparative Analysis of Arima and Facebook Prophet Algorithms for E-Commerce Product Sales Forecasting - Ferdinansyah, Ersha Thoriq; Roffi, Muhammad; Ramadhan, Rafi; Prasiwiningrum, Elyandri (Journal Collabits, 2026)
Uncertainty in market demand poses a fundamental challenge in e-commerce supply chain management. This study evaluates the accuracy of daily sales forecasting for the